What's in the balance?. (2nd December 2022) - Vollans, Caroline
Abstract : Work-life balance is a term we hear thrown around a lot. It is something that is good for us, indeed necessary. We all need a healthy work-life balance and should be striving for it. Or should we? Is it as simple as that?